Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Biodegradation of Polycyclic Aromatic Hydrocarbons by the Biofilm Forming Bacteria Priestia aryabhattai BMRS3B Isolated from the Rhizosphere of Oryza sativa - Ananthalekshmi L P; Soumya P; Radhakrishnan E K; Jayachandran K (Water, Air, & Soil Pollution, 2025)

Optimizing technical efficiency in whiteleg shrimp aquaculture: a double-bootstrap data envelopment analysis - Kalidoss Radhakrishnan; Baban Bayan; Swadesh Prakash; P. S. Ananthan; Anu Susan Sam; Sandip Shil; Arpita Sharma; Srichandan Das; Kota Karuna Sri (Aquaculture International, 2025)

Plant probiotic potential of rapid zinc-solubilizing Bacillus sp. VR in the presence of exogenously supplemented zinc oxide - P. Sruthi Parameswaran; V. K. Priya; K. Jayachandran; E. K. Radhakrishnan (Cereal Research Communications, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Unveiling Hidden Water Resources: Deep Learning and Remote Sensing for Subsurface Hydrology for Environmental Health - Jampani Satish Babu; Dinesh G.; R. Suganya; P. Radhakrishnan; Anand Sutar; Alex David S.; L. Malleswara Rao (Remote Sensing in Earth Systems Sciences, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Fluorescent N-Doped Carbon Dots as a Biocompatible Sensor for Thiophanate-Methyl Detection - K. Radhakrishnan; R. Suriyaprakash; L. Srimathi Priya; P. Saravanan; Mir Waqas Alam; Pitcheri Rosaiah; Guru Prakash Nunna; Tae Jo Ko (Journal of Fluorescence, 2025)

Enhanced biodegradation of chlorpyrifos in the presence of sub-inhibitory concentration of ZnONPs by Pseudomonas sp. CF7b - Sreekanth K.; P. Anjali; B.S. Akshatha; Riya Alex; E.K. Radhakrishnan (Process Safety and Environmental Protection, 2024)

Quantifying abnormal writing kinematics in writer’s cramp using a novel software platform - Kavadisseril Vivekanandan Vysakha; Vineeth Radhakrishnan; Praveen James; B. Suresh Kumar; Ashish Anand Susvirkar; Gangadhara Sarma; Ajith Cherian; K. P. Divya; Syam Krishnan Nair; Asha Kishore (Acta Neurologica Belgica, 2024)

Existence of rare actinobacterial forms in the Indian sector of Southern Ocean: 16 S rRNA based metabarcoding study - Radhakrishnan Manikkam; Manigundan Kaari; Abirami Baskaran; Meganathan P. Ramakodi; Gopikrishnan Venugopal; Parli Venkateswaran Bhaskar (Brazilian Journal of Microbiology, 2024)

Morphological, Metabolomic and Genomic Evidences on Drought Stress Protective Functioning of the Endophyte Bacillus safensis Ni7 - Silju Juby; P. Soumya; K. Jayachandran; E. K. Radhakrishnan (Current Microbiology, 2024)

Novel in-genome based analysis demonstrates the evolution of OmpK37, antimicrobial resistance gene from a potentially pathogenic pandrug resistant Klebsiella pneumoniae MS1 isolated from healthy broiler feces - Sreejith Sreekumaran; Priya V K; Manjusha Premnath; Prathiush P R; Anisha M N; Jyothis Mathew; Jayachandran K; Radhakrishnan E K (Science of The Total Environment, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Effects of Zinc Oxide Nanoparticles Supplementation on Growth Performance, Meat Quality and Serum Biochemical Parameters in Broiler Chicks - V. Mozhiarasi; R. Karunakaran; P. Raja; L. Radhakrishnan (Biological Trace Element Research, 2024)

Water budgeting for production of hatchlings, fry and fingerlings of Asian catfish, Clarias magur - S. Ferosekhan; P. Velmurugan; K. Radhakrishnan; S.P. Kamble; M.K. Bairwa; S.K. Sahoo; P.C. Das (Aquaculture, 2024)

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Unravelling the Parkinson’s puzzle, from medications and surgery to stem cells and genes: a comprehensive review of current and future management strategies - Krishnapriya Chandrababu; Vineeth Radhakrishnan; A. S. Anjana; Rahul Rajan; Unnikrishnan Sivan; Syam Krishnan; P. S. Baby Chakrapani (Experimental Brain Research, 2024)

Predicting Human Risk with Multidrug Resistant Enterobacter hormaechei MS2 having MCR 9 Gene Isolated from the Feces of Healthy Broiler Through Whole-Genome Sequence-Based Analysis - Sreejith Sreekumaran; Manjusha Premnath; P. R. Prathyush; Jyothis Mathew; Chitra C. Nath; Nimmy Paul; Swapna Susan Abraham; E. K. Radhakrishnan (Current Microbiology, 2024)

A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels - K. Radhakrishnan; P. Senthil Kumar; Gayathri Rangasamy; L. Praveen Perumal; S. Sanaulla; S. Nilavendhan; V. Manivasagan; K. Saranya (Fuel, 2023)

Experiments and Simulations to Study Transport and Structure of Foam in Rough Carbonate Fractures - Anuradha Radhakrishnan; Alex Gigliotti; Keith P. Johnston; David DiCarlo; Maša Prodanović (Transport in Porous Media, 2022)

Correction to: Elevation of TRPV1 expression on T-cells during experimental immunosuppression - P Sanjai Kumar; Tathagata Mukherjee; Somlata Khamaru; Anukrishna Radhakrishnan; Dalai Jupiter Nanda Kishore; Saurabh Chawla; Subhransu Sekhar Sahoo; Subhasis Chattopadhyay (Journal of Biosciences, 2022)

Assessment of urban air quality from Twitter communication using self-attention network and a multilayer classification model - Thushara Sudheish Kumbalaparambi; Ratish Menon; Vishnu P Radhakrishnan; Vinod P Nair (Environmental Science and Pollution Research, 2022)

Elevation of TRPV1 expression on T-cells during experimental immunosuppression - P Sanjai Kumar; Tathagata Mukherjee; Somlata Khamaru; Anukrishna Radhakrishnan; Dalai Jupiter Nanda Kishore; Saurabh Chawla; Subhransu Sekhar Sahoo; Subhasis Chattopadhyay (Journal of Biosciences, 2022)

Non-thermal technologies: Solution for hazardous pesticides reduction in fruits and vegetables - Ranjitha Gracy T. K.; Sharanyakanth P. S.; Mahendran Radhakrishnan (Critical Reviews in Food Science and Nutrition, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Rhizospheric Pseudomonas spp. with plant growth promotion and antifungal properties against Sclerotium rolfsii mediated pathogenesis in Vigna unguiculata - P Jishma; K Shibil Shad; EC Athulya; P Sachidanandan; EK Radhakrishnan (Plant Biotechnology Reports, 2021)

Evaluation of various image transformation techniques for the delineation of coastal sand dune features in Tamil Nadu, South India - Praveenraj Durai; Nisha P. Radhakrishnan; K. J. Sarunjith; Aparna S. Bhaskar (Earth Science Informatics, 2021)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Inhibition of transient receptor potential vanilloid 1 (TRPV1) channel regulates chikungunya virus infection in macrophages - P. Sanjai Kumar; Tapas K. Nayak; Chandan Mahish; Subhransu S. Sahoo; Anukrishna Radhakrishnan; Saikat De; Ankita Datey; Ram P. Sahu; Chandan Goswami; Soma Chattopadhyay; Subhasis Chattopadhyay (Archives of Virology, 2021)

Combined Effect of Pseudomonas spp. Consortium and Fertilizer with Micronutrients on Enhanced yield of Amaranthus tricolor (L.) - S. Soumya; S. Sreejith; K. Shibil Shad; P. Anusha; B. Swathy; R. Renikrishna; S. Saranya; P. Jishma; E. K. Radhakrishnan; A. Remakanthan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Modulation of agriculturally useful rhamnolipid profile of Pseudomonas sp. K6 due to the supplementation with chitosan and gold nanoparticles - P. Jishma; E. K. Radhakrishnan (World Journal of Microbiology and Biotechnology, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Correction to: Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2020)

Biofilm Changes of Clinically Isolated Coagulase Negative Staphylococci - K. R. Soumya; P. Jishma; Sheela Sugathan; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Role of Nanocurcumin as a Surface Modifying Agent with Excellent Preventive Effect on Device-Related CoNS Infections - K. R. Soumya; P. Jishma; R. Dhivya; Jamespandi Annaraj; Sheela Sugathan; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Highs and lows of cannabinoid-dopamine interactions: effects of genetic variability and pharmacological modulation of catechol-O-methyl transferase on the acute response to delta-9-tetrahydrocannabinol in humans - Mohini Ranganathan; Joao P. De Aquino; Jose A. Cortes-Briones; Rajiv Radhakrishnan; Brian Pittman; Savita Bhakta; Deepak C. D’Souza (Psychopharmacology, 2019)

Advances in the development and use of DREB for improved abiotic stress tolerance in transgenic crop plants - Tanmoy Sarkar; Radhakrishnan Thankappan; Gyan P. Mishra; Bhagwat D. Nawade (Physiology and Molecular Biology of Plants, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Plant Growth Promoting Endophytic Serratia sp. ZoB14 Protecting Ginger from Fungal Pathogens - Rohini Sabu; R. Aswani; P. Jishma; B. Jasim; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Accumulation of Heavy Metals in Some Marine Fisheries Resources Collected from Gulf of Mannar Marine Biosphere Reserve, Southeast Coast of India - S. Rameshkumar; P. Prabhakaran; K. Radhakrishnan; R. Rajaram (Proceedings of the Zoological Society, 2018)

Dietary Supplement of Medicinal Herbal Leaf Powder on Growth Performance, Digestive Enzymes Activities, Energy Utilization and Vitamin Levels of the Freshwater Prawn Macrobrachium rosenbergii - T. Muralisankar; P. Saravana Bhavan; S. Radhakrishnan; P. Santhanam (Proceedings of the Zoological Society, 2018)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Culturable Endophytic Bacteria of Ginger Rhizome and their Remarkable Multi-trait Plant Growth-Promoting Features - Sabu Rohini; R. Aswani; M. Kannan; V. P. Sylas; E. K. Radhakrishnan (Current Microbiology, 2018)

Endophytic Paraconiothyrium sp. from Zingiber officinale Rosc. Displays Broad-Spectrum Antimicrobial Activity by Production of Danthron - C. Anisha; P. Sachidanandan; E. K. Radhakrishnan (Current Microbiology, 2018)

DNAzyme Based Amplified Biosensor on Ultrasensitive Fluorescence Detection of Pb (II) Ions from Aqueous System - A. Ravikumar; P. Panneerselvam; K. Radhakrishnan; Norhashimah Morad; C. D. Anuradha; S. Sivanesan (Journal of Fluorescence, 2017)

Photochemical Degradation of Curcumin: a Mechanism for Aqueous Based Sensing of Fluoride - Roopa Venkataraj; C. P. Girijavallabhan; P. Radhakrishnan; V. P. N. Nampoori; M. Kailasnath (Journal of Fluorescence, 2017)

Suppression of Baseline Wander Artifact in Magnetocardiogram Using Breathing Sensor - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)

Does obstructive sleep apnea correlate with Epworth Sleepiness Scale in an Indian population? - Sapna Erat Sreedharan; Anupa A. Vijayakumari; Pragati Agrawal; Gopal Krishna Dash; Shana N. Nair; J. P. Unnikrishnan; Ravi Prasad Varma; Ashalatha Radhakrishnan (Sleep and Biological Rhythms, 2017)

Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)
Electroencephalography (EEG) is a non-invasive way of recording brain activities, making it useful for diagnosing various neurological disorders. However, artifact signals associated with eye blinks or the heart spread across the scalp, contaminating EEG recordings and making EEG data analysis difficult. To solve this problem, we implement a common methodology to suppress both cardiac and ocular artifact signal, by correlating the measured contaminated EEG signals with the clean reference electro-oculography (EOG) and electrocardiography (EKG) data and subtracting the scaled EOG and EKG from the contaminated EEG recording. In the proposed methodology, the clean EOG and EKG signals are extracted by subjecting the raw reference time-series data to ensemble empirical mode decomposition to obtain the intrinsic mode functions. Then, an unsupervised technique is used to capture the artifact components. We compare the distortion introduced into the brain signal after artifact suppression using the proposed method with those obtained using conventional regression alone and with a wavelet-based approach. The results show that the proposed method outperforms the other techniques, with an additional advantage of being a common methodology for the suppression of two types of artifact.

Development of a multiplex RT-PCR for simultaneous diagnosis of human metapneumovirus (HMPV) and human respiratory syncytial virus (HRSV) from clinical specimens - Seetha Dayakar; Heera R. Pillai; Vineetha P. Thulasi; Radhakrishnan R. Nair (VirusDisease, 2016)

Spectral and Lensing Characteristics of Gel-Derived Strontium Tartrate Single Crystals Using Dual-Beam Thermal Lens Technique - I. Rejeena; V. Thomas; S. Mathew; B. Lillibai; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Spectral and Non Radiative Decay Studies of Lead Di Bromide Single Crystals by Mode Matched Thermal Lens Technique - I. Rejeena; B. Lillibai; V. Thomas; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Transgenic peanut overexpressing mtlD gene confers enhanced salinity stress tolerance via mannitol accumulation and differential antioxidative responses - Kirankumar G. Patel; Viralkumar B. Mandaliya; Gyan P. Mishra; Jentilal R. Dobaria; Radhakrishnan Thankappan (Acta Physiologiae Plantarum, 2016)

Effects of Probiotics on Survival, Growth and Digestive Enzymes Activities in Freshwater Prawn Macrobrachium rosenbergii (De Man 1879) - C. Seenivasan; S. Radhakrishnan; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2016)

Population genetic structure of the shovel-nosed lobster Thenus unimaculatus (Decapoda, Scyllaridae) in Indian waters based on RAPD and mitochondrial gene sequences - N. S. Jeena; A. Gopalakrishnan; J. K. Kizhakudan; E. V. Radhakrishnan; Raj Kumar; P. K. Asokan (Hydrobiologia, 2016)

Phytostimulatory and hardening period-reducing effects of plant-associated bacteria on micropropagated Musa acuminata cv. Grand Naine - E. P. Suada; B. Jasim; C. J. Jimtha; G. P. Gayatri; E. K. Radhakrishnan; A. Remakanthan (In Vitro Cellular & Developmental Biology - Plant, 2015)

Effect of endophytic Bacillus sp. from selected medicinal plants on growth promotion and diosgenin production in Trigonella foenum-graecum - B. Jasim; P. R. Geethu; Jyothis Mathew; E. K. Radhakrishnan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Influence of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii Post-larvae - C. Seenivasan; S. Radhakrishnan; R. Shanthi; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2015)

Solvent Dependency in the Quantum Efficiency of 4-[(4-Aminophenyl)-(4-imino-1-cyclohexa-2, 5- dienylidene) methyl] Aniline Hydrochloride - Bini Pathrose; V. P. N. Nampoori; P. Radhakrishnan; H. Sahira; A. Mujeeb (Journal of Fluorescence, 2015)

Isolation of endophytic bacteria from embryogenic suspension culture of banana and assessment of their plant growth promoting properties - John C. Jimtha; P. V. Smitha; C. Anisha; Thomas Deepthi; George Meekha; E. K. Radhakrishnan; G. P. Gayatri; A. Remakanthan (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Measurement of Absolute Fluorescence Quantum Yield of Basic Fuchsin Solution Using a Dual-Beam Thermal Lens Technique - Bini Pathrose; V. P. N. Nampoori; P. Radhakrishnan; A. Mujeeb (Journal of Fluorescence, 2014)

Influence of medicinal herbs (Alteranthera sessilis, Eclipta alba and Cissus quadrangularis) on growth and biochemical parameters of the freshwater prawn Macrobrachium rosenbergii - S. Radhakrishnan; P. Saravana Bhavan; C. Seenivasan; R. Shanthi; R. Poongodi (Aquaculture International, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Direct and Indirect Validation of Potential Fishing Zone Advisory off the Coast of Uttara Kannada, Karnataka - Sanjeev P. Deshpande; K. V. Radhakrishnan; U. Gopalakrishna Bhat (Journal of the Indian Society of Remote Sensing, 2011)

Shifting of Fluorescence Peak in CdS Nanoparticles by Excitation Wavelength Change - S. Mathew; Santhi Ani Joseph; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2011)

Low-frequency internal waves and their influence on transmission loss variability - P. V. Hareesh Kumar; A. Raghunadha Rao; K. Anilkumar; M. Padmanabham; K. G. Radhakrishnan (Natural Hazards, 2011)

Study of changes in bacterial and viral abundance in formaldehyde-fixed water samples by epifluorescence microscopy - Ammini Parvathi; Seetha Radhakrishnan; M. P. Sajila; Breezy Jacob (Environmental Monitoring and Assessment, 2011)

Thermodynamics of chromium(III) adsorption onto a cation exchanger derived from saw dust of Jack wood - T. S. Anirudhan; P. G. Radhakrishnan (Environmental Chemistry Letters, 2011)

Diversity-oriented, one-pot, multi-component synthesis of substituted uracil derivatives - Yogesh Y. Pedgaonkar; Mariam S. Degani; Radhakrishnan P. Iyer (Molecular Diversity, 2011)

Leaf-eating caterpillar ( Opisina arenosella)-induced yield loss in coconut palm - Chandrika Mohan; C.P. Radhakrishnan Nair; C. Kesavan Nampoothiri; P. Rajan (International Journal of Tropical Insect Science, 2010)

Comparative study of interspecific genetic divergence and phylogenic analysis of genus Jatropha by RAPD and AFLP - D. V. N. Sudheer Pamidiamarri; Nirali Pandya; Muppala P. Reddy; T. Radhakrishnan (Molecular Biology Reports, 2009)

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)

Genetic association analysis of KCNQ3 and juvenile myoclonic epilepsy in a South Indian population - J. Vijai; A. Kapoor; H. M. Ravishankar; P. J. Cherian; A. S. Girija; B. Rajendran; G. Rangan; S. Jayalakshmi; S. Mohandas; K. Radhakrishnan; A. Anand (Human Genetics, 2003)

Absence ofGABRA1 Ala322Asp mutation in juvenile myoclonic epilepsy families from India - A. Kapoor; J. Vijai; H. M. Ravishankar; P. Satishchandra; K. Radhakrishnan; A. Anand (Journal of Genetics, 2003)

Control of the coconut pest Oryctes rhinoceros L. using the Oryctes virus - Murali Gopal; Alka Gupta; B. Sathiamma; C. P. Radhakrishnan Nair (International Journal of Tropical Insect Science, 2001)